2000
DOI: 10.1016/s0169-555x(99)00062-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of shore platforms on Kaikoura Peninsula, South Island, New Zealand

Abstract: Shore platforms on the Kaikoura Peninsula have been examined to determine the roles of marine and subaerial weathering processes in platform evolution. Erosion was measured to assess rates of development and processes of erosion. Lowering rates on platforms are presented from two years of monitoring using a traversing micro-erosion meter. Cliff retreats were calculated using aerial photographic interpretation. Marine processes were investigated by using deep water wave data, by measuring waves on shore platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
158
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(169 citation statements)
references
References 43 publications
10
158
1
Order By: Relevance
“…More broadly, on rocky platforms the thermal and hygric influences of encrusting species may mediate episodic and rapid (block-scale) erosion (e.g., Naylor et al, 2012) and alter rates of topographic evolution via subaerial weathering (e.g., Moura et al, 2012;Stephenson and Kirk, 2000). As well as further work on barnacles, more evidence for the roles of other common encrusting species (such as mussels and …”
Section: Discussionmentioning
confidence: 95%
“…More broadly, on rocky platforms the thermal and hygric influences of encrusting species may mediate episodic and rapid (block-scale) erosion (e.g., Naylor et al, 2012) and alter rates of topographic evolution via subaerial weathering (e.g., Moura et al, 2012;Stephenson and Kirk, 2000). As well as further work on barnacles, more evidence for the roles of other common encrusting species (such as mussels and …”
Section: Discussionmentioning
confidence: 95%
“…The general absence of such features on the jointed surfaces closer to low-tide level could relate to the enhanced downwearing along the joint planes inhibiting the formation of larger pits, or a reduction in the frequency of wetting and drying cycles. Stephenson and Kirk (2000b) suggested that the greatest downwearing occurred within these wetting and drying zones, which they said occurred across the intertidal zone. A long-term data set of vertical erosion rates would, however, be needed to quantify the exact relationship between wetting and drying and downwearing at Shag Point.…”
Section: Discussionmentioning
confidence: 99%
“…On rocky coasts, and particularly on chalky coasts, cliffs may retreat as fast as 20 cm/yr, while the shore platform undergoes downwearing (e.g., Stephenson and Kirk, 2000a;Stephenson and Kirk, 2000b;Trenhaile and Byrne, 1986). The processes responsible include: chemical weathering during tide water level fluctuations (Duperret et al, 2005;Kanyaya and Trenhaile, 2005;Stephenson and Kirk, 2000a;Sunamura, 1992), biological action (e.g., Nesteroff and Mélières, 1967), and the mechanical action of waves (e.g., de Lange and Moon, 2005;Stephenson and Kirk, 2000b).…”
Section: Brief Overview Of Processes Driving Coastal Erosionmentioning
confidence: 99%
“…The processes responsible include: chemical weathering during tide water level fluctuations (Duperret et al, 2005;Kanyaya and Trenhaile, 2005;Stephenson and Kirk, 2000a;Sunamura, 1992), biological action (e.g., Nesteroff and Mélières, 1967), and the mechanical action of waves (e.g., de Lange and Moon, 2005;Stephenson and Kirk, 2000b). On chalky coasts along the English Channel, these processes result in a roughly linear coastline in plan-view, and a very shallowly sloping shore platform (typically ~1:150).…”
Section: Brief Overview Of Processes Driving Coastal Erosionmentioning
confidence: 99%